2018
DOI: 10.7287/peerj.preprints.3511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the sugar receptor IR60b for Drosophila melanogaster: A hypothesis

Abstract: In a recent paper, Joseph and colleagues (Joseph et al., 2017) have characterized the selective sucrose receptor IR60b in Drosophila, and proposed that it serves to limit sucrose consumption, and thus to prevent overfeeding. Here, we propose an alternative hypothesis for this sucrose receptor. Adult fruit flies feed by excreting saliva onto the food, and imbibing the predigested liquefied food, or by filling the crop, where the food is predigested. Enzymes in the saliva hydrolyse starch and disacharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Since the flies used in this study was fed with diet supplemented with sucrose, it is therefore paramount to assay for the activities of carbohydrate hydrolyzing enzymes. Report has shown that amylase and sucrase are the major carbohydrate hydrolyzing enzymes found in fruit fly (Haloi, Hasan, & Boro, 2014; Szyszka & Galizia, 2018). α‐amylase is involved in the hydrolysis of starch and other polysaccharides to disaccharides and α‐glucosidase is responsible for the breakdown of disaccharides such as sucrose to absorbable monosaccharides in living organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Since the flies used in this study was fed with diet supplemented with sucrose, it is therefore paramount to assay for the activities of carbohydrate hydrolyzing enzymes. Report has shown that amylase and sucrase are the major carbohydrate hydrolyzing enzymes found in fruit fly (Haloi, Hasan, & Boro, 2014; Szyszka & Galizia, 2018). α‐amylase is involved in the hydrolysis of starch and other polysaccharides to disaccharides and α‐glucosidase is responsible for the breakdown of disaccharides such as sucrose to absorbable monosaccharides in living organisms.…”
Section: Resultsmentioning
confidence: 99%
“…For example, IR52c and IR52d are expressed in sexually-dimorphic populations of leg neurons and implicated in male courtship behaviours 26 , although their ligands are unknown. Reporters for IR60b, IR94f and IR94h are co-expressed in pharyngeal GSNs that respond to sucrose, which may limit overfeeding 29 or monitor the state of externally digested food 30 . IR62a is essential for behavioural avoidance of high Ca 2+ concentrations, but the precise neuronal expression of this receptor is unclear 31 .…”
Section: Introductionmentioning
confidence: 99%